2012
DOI: 10.1063/1.4746796
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory regularity of charge carrier traps energy spectra in silicon organic polymer poly(di-n-hexylsilane)

Abstract: Charge carrier traps energy spectra have been investigated in silicon organic polymer poly(di-n-hexylsilane) by fractional thermally stimulated luminescence in the temperature range from 5 to 200 K. The energy spectrum of traps has been found to be discrete in nature, not the quasi-continuous, as it was considered earlier. It has been established that the traps energies form two characteristic series resulting from the vibrational quanta at 373 and 259 cm -1 , respectively. It is important that these vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…2), which was predicted by the model developed in [20]. The model suggested in [19] cannot explain the coincidence of the activation energy with the energy of vibrations. Therefore, we use the model suggested in [20], which explains this coincidence and predicts the appearance of the structure.…”
Section: Experimental Results Determination Of the Activation Energymentioning
confidence: 91%
See 2 more Smart Citations
“…2), which was predicted by the model developed in [20]. The model suggested in [19] cannot explain the coincidence of the activation energy with the energy of vibrations. Therefore, we use the model suggested in [20], which explains this coincidence and predicts the appearance of the structure.…”
Section: Experimental Results Determination Of the Activation Energymentioning
confidence: 91%
“…This makes it possible to increase the registration sensitivity by 2-3 orders of magnitude, as compared with that used for the detection of the integral TSL curves of other polymers. As a result, this allows one to get more than 85 heating fractions in the temperature range of 5-40 K. It was noted that the maximum number of fractions within the traditional methods [21,22] was not more than 20-30 fractions in the temperature range [18,19].…”
Section: Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The authors of a number of papers [2,3] reported that molecular movements play a role in the carrier release from traps and that finds manifestation in the thermoluminescence. Unusual results were obtained in the works [4,5] devoted to the investigation of poly(di-n-hexylsilane) at low temperatures by the fractional TSL. The results showed the presence of pronounced discrete levels, though the spectrum of localized states in the polymer free from impurities or defects should be quasi-continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Usually this process involves many vibrations and describes by the Arrhenius formula exp(−|E a |/κT), where T is the temperature, E a is the activation energy. The peculiarities observed in experiments [4,5] were explained in [8] under assumption of the existence of a process, in which a release of carrier from a trap may occur via the absorption by carrier of the separate quantum of molecular vibration with energy equal to the activation energy of the carrier. It explain the coincidence of the activation energy and the energy of the quantum of molecular vibrations obtained from Raman spectra.…”
Section: Introductionmentioning
confidence: 99%